2023
DOI: 10.1039/d2bm01493a
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable hydrogels with photodynamic antibacterial activity promote wound healing and mitigate scar formation

Abstract: Bacterial proliferation and disordered extracellular matrix (ECM) at the wound site are major reasons for delayed healing and abnormal scarring. The development of new multifunctional dressing materials that can effectively...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Since that bacterial proliferation at the wound site is one of the major reasons for delayed healing and abnormal scarring ( Frykberg and Banks, 2015 ; Zhang et al, 2022 ), and Gallium and Quercetin are documented of anti-bacterial property ( Hu et al, 2022 ; Qin J. et al, 2022 ), we went on to investigate whether QCT@GNP-Ga exerted great anti-bacterial effect. The surface of the agarose medium was coated with QCT@GNP-Ga and then inoculated with S. aureus and E. coli to observe its anti-bacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Since that bacterial proliferation at the wound site is one of the major reasons for delayed healing and abnormal scarring ( Frykberg and Banks, 2015 ; Zhang et al, 2022 ), and Gallium and Quercetin are documented of anti-bacterial property ( Hu et al, 2022 ; Qin J. et al, 2022 ), we went on to investigate whether QCT@GNP-Ga exerted great anti-bacterial effect. The surface of the agarose medium was coated with QCT@GNP-Ga and then inoculated with S. aureus and E. coli to observe its anti-bacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…These materials are becoming important as a promising solution for wound management due to their tunability, softness, permeability, biocompatibility, or biodegradability. In the context of drug delivery, hydrogels benefit from their porosity, which enables drug encapsulation within a 3D polymeric network. Some antibacterial hydrogels have been particularly valuable in the context of light-induced therapies such as antimicrobial photodynamic therapy (aPDT). aPDT combines light, molecular oxygen, and a photosensitizer to generate reactive oxygen species (ROS) that oxidize lipids, proteins, DNA, and other biomolecules, leading to bacterial inactivation. Good transparency is, therefore, needed for hydrogels to perform well in aPDT, especially for wound dressing applications, and previous work has focused on optimizing their optical properties. , It was shown that electron-beam polymerized polyethylene glycol diacrylate (PEGDA) hydrogels have a higher transmittance over a broader wavelength range compared to their UV-cured counterparts, reaching values well above 90% …”
Section: Introductionmentioning
confidence: 99%
“…[23,24] It has been demonstrated that verteporfin-mediated PDT is efficient in producing ROS and killing bacteria. [25,26] Furthermore, verteporfin is regarded as an inhibitor of the Hippo-Yes-associated protein-1 (YAP) signaling pathway, which plays an important role in regulating the proliferation, apoptosis, and an-giogenesis of endothelial cells (ECs). [27,28] It has been reported that verteporfin is able to inhibit the angiogenesis of ECs without light activation.…”
Section: Introductionmentioning
confidence: 99%